How do secondary mathematics teachers use textbooks in teaching: A case study from China - Jiajie Yan (International Journal of Education and Learning, 2024)
The method of using mathematics textbooks for teaching impacts their effectiveness as a learning and teaching medium. Therefore, it is essential to understand how to use mathematics textbooks effectively. Based on this background, this study aims to analyze the use of mathematics textbooks by an experienced Junior High School mathematics teacher in the classroom. The content analysis method is employed to compare the textbooks with the teaching materials actually used by teachers in terms of teaching content and design sequence. Teachers generally recognize the content of mathematics textbooks well and utilize most of the contents. However, the textbook content is often split, reorganized, supplemented, and deleted during use. Furthermore, teachers adjust the teaching sequence based on the textbooks. This indicates that teachers effectively redesign textbooks in their application. This research suggests that teachers should not use mathematics textbooks directly but should adapt them to fit their respective schools' contexts.